Every Dog in the Neighborhood - Stead, Philip Christian; Cordell, Matthew, 1975- (New York : Holiday House, 2022)
Louis and his eccentric Grandmother set out to count every dog in the neighborhood when they find out about city halls woefully inadequate record keeping.
"Neal Porter Books."
Ages 4 to 8
Grades K-1
Keywords: Grandparent and child -- Juvenile fiction; Neighborhoods -- Juvenile fiction; Dogs -- Juvenile fiction; Pets -- Juvenile fiction; Grandparent and child -- Fiction; Neighborhoods -- Fiction; Dogs -- Fiction; Pets -- Fiction; Picture books